Representativeness impacts on accuracy and precision of climate spatial interpolation in data-scarce regions - Bhowmik, Avit Kumar (2019)
Bhowmik, A. K., & Costa, A. C. (2015). Representativeness impacts on accuracy and precision of climate spatial interpolation in data-scarce regions. Meteorological Applications, 22(3), 368-377. https://doi.org/10.1002/met.1463